2020
DOI: 10.3390/medicina56090465
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Recurrence after Catheter Ablation of Paroxysmal Atrial Fibrillation in Different Follow-Up Periods

Abstract: Background and objectives: Pulmonary vein (PV) reconnection is a major reason for recurrence after catheter ablation of paroxysmal atrial fibrillation (PAF). However, the timing of the recurrence varies between patients, and recurrence >1 year after ablation is not uncommon. We sought to elucidate the characteristics of atrial fibrillation (AF) that recurred in different follow-up periods. Materials and Methods: Study subjects comprised 151 consecutive patients undergoing initial catheter ablation of PAF. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The concept of “AF begets AF” underscores the challenge of managing prolonged AF states [18]. Current research has demonstrated a significant correlation between pre-procedure AF duration and post-RFCA recurrence rates [19, 20]. One study has indicated that longer AF duration significantly increases the recurrence rate, especially among patients with persistent AF lasting over three years [10].…”
Section: Discussionmentioning
confidence: 99%
“…The concept of “AF begets AF” underscores the challenge of managing prolonged AF states [18]. Current research has demonstrated a significant correlation between pre-procedure AF duration and post-RFCA recurrence rates [19, 20]. One study has indicated that longer AF duration significantly increases the recurrence rate, especially among patients with persistent AF lasting over three years [10].…”
Section: Discussionmentioning
confidence: 99%
“…Third, some clinical studies have found that elevated ANP, or midregional N‐terminal pro‐ANP, type B natriuretic peptide, and N‐terminal pro‐BNP levels were significantly associated with the risk factor of AF recurrence after ablation. 54 , 55 , 56 , 57 , 58 We did not discuss the association between those factors and recurrent AF after ablation. Fourth, plasma corin levels are correlated with immediate heart rhythm, as confirmed by higher concentrations in AF than in sinus rhythm.…”
Section: Discussionmentioning
confidence: 99%
“…The basic post-ablation monitoring strategy recommended by the HRS/EHRA/ECAS expert consensus statement [2] includes a 12-lead electrocardiogram (ECG) at a minimum of three visits (at 3, 6, and 12 months) and 24-hour Holter monitoring at the end of the follow-up period (12 months). In addition to the scheduled ECG recording, timely medical contact whenever symptoms occur is recommended for the detection of symptomatic episodes [3][4][5]. However, symptoms may resolve before…”
mentioning
confidence: 99%